Trans-Terminalization as a Linguistic-Cognitive Process - L. M. Alekseeva; S. L. Mishlanova; E. V. Yakovleva (Научный диалог, 2025)
This study investigates the nominative processes within contemporary terminological systems. A review of existing literature reveals a contradiction between the cognitive nature of trans-terminalization and the limited potential of structural approaches to its investigation. The research material comprises trans-terminalized units from the terminology of assisted reproductive technologies, sourced from recent scientific articles and monographs. It is argued that the domain of assisted reproductive technologies falls under the “umbrella” of the broader knowledge area of bioethics, which regulates the relationship between all forms of life and various technologies. The study emphasizes that additional conceptual structures — financial, legal, and moral-ethical — are involved in the realm of assisted reproductive technologies, similar to those in bioethics, aimed at regulating the impact of science and technology. Cognitive semantic methods, such as frame analysis and conceptual integration modeling, are employed to explore trans-terminalization. It is demonstrated that trans-terminalization is a linguistic-cognitive phenomenon present in secondary terminological systems of complex fields of knowledge, manifested through active lexical-semantic processes in both the borrowed terms and the units of the adapting terminological system